Background suppression with dual modulation by saturated absorption competition microscopy. (December 2021) - Li, Chuankang; Zhou, Renjie; Wang, Wensheng; Zhan, Zhengyi; Zhang, Zhimin; Li, Yuhang; Li, Yuzhu; Hao, Xiang; Kuang, Cuifang; Liu, Xu
Highlights: In this report, we propose a novel approach by simultaneously modulating the two beams of SAC with two distinct frequencies, called dual-modulation SAC (dmSAC). In dmSAC modality, the homodyne detection would not identify the uncorrelated fluorescence, the image background could be free. We have experimentally demonstrated the dependences of the background contribution on the modulation frequencies and spatial resolution as high as one seventh of the illumination wavelength is gained. dmSAC is believed to hold great potential in biological and physical applications and to become another powerful tool for the study of the micro world through the follow-up researches. Abstract: Optical super-resolution microscopy can break the diffraction limit in far-field imaging to achieve nanoscopic resolution. Nowadays, super-resolution imaging based on saturated excitation exhibits great potentials in extracting high-frequency components. Current saturated absorption competition (SAC) method is based on spatio-temporally modulating the incident laser beams and demodulating the target fluorescence at a particular frequency. However, the uncorrelated background noise spoils the imaging performance and sets an upper limit to the attainable spatial resolution. Here, we propose a novel approach by simultaneously modulating the two beams of SAC with two distinct frequencies, called dual-modulation SAC (dmSAC). In dmSAC, the homodyne detection will not pick up uncorrelated fluorescence signals, therefore, the image is free of background noise. This technique has the potential to enable super-resolution imaging with fluorescent and non-fluorescent probes, which may remain out of reach to fluorescence-based imaging methods.